Pemberdayaan Masyarakat melalui Pemanfaatan Singkong oleh Ibu-Ibu UP2K Desa Rantau Kasih, Kabupaten Musi Banyuasin - Leni Utami; Eni Murdiati; Muslimin Muslimin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research raises issues about community empowerment in increasing family income. The purpose of this research is to find out the strategy of community empowerment through the utilization of cassava by UP2K mothers in Rantau Kasih Village, and to find out the supporting and inhibiting factors that affect the empowerment program in increasing family income. This research is descriptive qualitative research. Data collection techniques in this study used observation, interviews and documentation. The results of this study indicate that community empowerment through the utilization of cassava by UP2K mothers has been able to increase family income. This can be seen from the increase in sales as a result of the utilization of cassava by UP2K women. This success is also supported by the process and stages of community empowerment that are carried out optimally. In addition, there are also supporting factors that influence the success of community empowerment activities through cassava utilization in Rantau Kasih village, lawang wetan sub-district, musi banyuasin district.